2015
DOI: 10.4236/ijcns.2015.811038
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Trust and Payment Methods: An Empirical Study of MarkaVIP Company

Abstract: This empirical study focused on investigating the perceived trust surrogated by a number of hypothesized factors and its effect on the choice of method of payment. The data were collected using a questionnaire, as the instrument for the primary data collection, with total collected back responses of 214 from customers of MarkaVIP. Structural equation modeling technique was used to fully analyze the data in order to determine what level of the relationship between the constituting factors of the perceived trust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
0
22
1
1
Order By: Relevance
“…Currently, adopting online learning in higher education during COVID-19 Pandemic had a significant impact on learners, educators and learning performance (Ustun 2020). Many research studies examined the impact of using online learning systems on university student's satisfaction and academic performance (Kapasia et al 2020) (Maqableh et al 2015). However, there is a need to understand the factors that positively or negatively influence students' academic performance from the use of the Internet.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, adopting online learning in higher education during COVID-19 Pandemic had a significant impact on learners, educators and learning performance (Ustun 2020). Many research studies examined the impact of using online learning systems on university student's satisfaction and academic performance (Kapasia et al 2020) (Maqableh et al 2015). However, there is a need to understand the factors that positively or negatively influence students' academic performance from the use of the Internet.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, COD is perceived as a prioritized alternative for online shopping. Studies from various backgrounds have indicated that privacy and security are the main factors which make customers reluctant toward using other e-payment methods (Maqableh et al, 2015;Mekovec & Hutinski, 2012;Ponte et al, 2015). E-commerce is still evolving in Pakistan and the customers lack prior experience of online payments.…”
Section: E-commerce and Payment Methodsmentioning
confidence: 99%
“…Perceived trust in the payment system is shown to have a positive effect on the usage of digital modes of payment [ 13 ]. While the central bank and banks are traditional regulators and service providers of payments systems respectively, non-banks have also emerged as new players in the framework.…”
Section: Related Literaturementioning
confidence: 99%